Analysis of the Effect of By-pass Pumping System Application on the Efficiency of the Pump and Process - Edwin Eka Yanuar; Setyo Nugroho (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Bypass system is a system of fluid flow with curves that cut off part of the main stream and usually use at piping system industry when repair and replace the instrument system. Bypass system is used for instrument replacement because it can take place without shuting down or cuting off. An ideas to utilize bypass system is used in the study design of the bypass pumping system by cutting partially discharge flow toward suction, it has potential to increase the velocity of flow and rotation of pump. Evaluation bypass, valve setting, the arrangement of pumps and pump motor speed regulation is a step to improve the efficiency of the pump. From the many usage of bypass system, a study to determine its effect on the efficiency of the pump is the right step to obtain efficient fluid systems. In this research, design of the bypass system module uses two angle variation there are 450 with elbow 450 and 900. Also the variation in the flow bypass valve opening to get the value of BEP (Best Efficiency Point) and the best bypass system design. At the end of the project is expected to be obtained bypass system design with a smaller head loss and increase the pump efficiency more than 5%.